The Effect of Audit Quality, Leverage, and Voluntary Disclosure on Real Earnings Management - Haryono Umar; Rani Ayu; Agustina Indriani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to examine the effect of leverage, audit quality, and voluntary disclosure on the real earnings management. The study used secondary data obtained from the annual report for the period of 2017 to 2019. The data were previously processed by the company and were available on the Indonesia Stock Exchange website. The analysis results show that voluntary disclosure, audit quality, and leverage have a significantly negative effect on real earnings management. Besides, voluntary disclosure, audit quality, and leverage simultaneously affect real earnings management.